1984
DOI: 10.1098/rstb.1984.0106
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic variation in its biological context

Abstract: The biology of antigenic variation is discussed, and the problems that must be solved to provide a full understanding of antigenic variation are considered. These are (i) the induction of v.s.g. synthesis in the salivary glands of the tsetse fly; (ii) the nature of the restriction on v.s.g. genes that allows only some of them to be expressed in the salivary glands; (iii) the nature of 'predominance' in v.s.g. expression in the mammalian host, and the mechanism by which it operates; (iv) the repression of v.s.g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1985
1985
2009
2009

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(1 citation statement)
references
References 65 publications
1
0
0
Order By: Relevance
“…This study does support the plasma membrane location reported originally by Turner [20]. However, our evidence also demonstrates that the GPI-PLC is mainly restricted to a small sub-domain of the plasma membrane covering the flagellum in both long-slender and short stumpy forms.…”
Section: Discussionsupporting
confidence: 90%
“…This study does support the plasma membrane location reported originally by Turner [20]. However, our evidence also demonstrates that the GPI-PLC is mainly restricted to a small sub-domain of the plasma membrane covering the flagellum in both long-slender and short stumpy forms.…”
Section: Discussionsupporting
confidence: 90%